Best Proximity Coincidence Point Results for α,D-Proximal Generalized Geraghty Mappings in JS-Metric Spaces - Atit Wiriyapongsanon; Phakdi Charoensawan; Tanadon Chaobankoh (Journal of Function Spaces)
We introduce a type of Geraghty contractions in a JS-metric space X, called α,D-proximal generalized Geraghty mappings. By using the triangular-α,D-proximal admissible property, we obtain the existence and uniqueness theorem of best proximity coincidence points for these mappings together with some corollaries and illustrative examples. As an application, we give a best proximity coincidence point result in X endowed with a binary relation.